Overview of the Use of Oralit and Zinc in Children with Diarrhea at the Community Health Center: Gambaran Penggunaan Oralit dan Zinc Pada Anak Penderita Diare Di Puskesmas - Nur Jaya; Ni Nyoman Lisna Saskia (Indonesian Journal of Innovation Multidisipliner Research, 2023)
Diarrhea is still one of the main problems can cause illness and death, especially in children. Diarrhea is an infectious disease caused by bacteria, virus or other microorganism which is characterized by abnormal frequency of defecation, 3 or more times in 24 hours with a soft feces consistency, the presence or absence of blood or foam in the feces. Giving oralit and zinc can reduce the incidence of diarrhea in children. The aim of this study was to determine the description of the use oralit and zinc in children suffering from diarrhea at the kawatuna Community Health Center during the peroid October 2022-March 2023. Method of this study is retrospective descriptive using secondary data, namely prescription sheets for pediatric patients with diarrhea who received oralit and zinc therapy. The research results showed that the population of diarrhea cases was 125 and the sample used was 96 cases. The highest use of oralit and zinc for treating casess of diarrhea is in October 2022 and the least in March 2023. The age of children most a affected by diarrhea is 1-6 months (50%) and the age least affected by diarrhea is 12-17 years (7,3%).